Lipschitz continuous points of functions on an interval - Zhekai Shen (Examples and Counterexamples)
In this paper, we address the problem of finding functions with predetermined Lipschitz continuous points. More precisely, given A⊆[0,1], we are interested in the existence of function f:[0,1]→R which is Lipschitz continuous exactly on A. Our result is related to Liouville numbers.